Legitimación activa de los adolescentes para limitar, suspender y privar la patria potestad con el fin de garantizar su derecho prioritario e interés superior - Puga Zapata, Rosa Elvira (2023)
My research topic entitled: "Active Legitimation of Adolescents to limit, suspend and Deprive Parental Authority In order to Guarantee their Priority right and Superior Interest",worldwide the different states seek that the rights of minors are respected, which has led them over time to develop standards that guarantee the integral development of children and adolescents, along with the evolution of society, thus providing greater participation to minors in judicial processes in which their rights are determined, despite this, there are still limitations in certain circumstances in which they cannot go directly to the Judicial Units in order to safeguard their rights, as in the case of limitation, suspension and deprivation of parental authority against their parents, in the event of a violation of rights or omission of the duties that the parents have to laugh with their children. In this sense, the present thesis entitled: "Active legitimation of adolescents to limit, suspend and deprive parental authority in order to guarantee their priority right and superior interest" specifies that adolescents have sufficient reason to go to a Judicial Unit and request the limitation, suspension and deprivation of parental authority, where the technical or first reception offices accompany and facilitate the processing of the case, where prior to establishing the judicial process, the corresponding assessments are made by the experts that make up the office technique of the Council of the Judiciary, in the sense of clarifying the facts that motivate the adolescent as well as to provide judges with clarity of the facts. Finally, through the methodology used, that is: surveys, interviews, comparative law, doctrine, together with scientific data, it is shown that adolescents have sufficient capacity and reasoning to be able to request compliance with the rights that arise from the homeland power, safeguarding rights recognized in the constitution and other national regulations. Keywords: active legitimation, parental authority, reasoning